Le shintō sécularisé de la restauration de Meiji - Aurélien Allard (Ebisu: Études Japonaises)
The requalification and reorganization of places of worship implemented during the early years of the Meiji Restoration (1868–1871) by the government can be interpreted through the framework of secularization. While many scholars specializing in modern and contemporary Shintō view the kokutai policy as the foundation of a state religion, the measures applied to local temples and shrines suggest a process of secularization. This study aims to achieve two primary objectives: first, to highlight the secular and non-religious character of the state’s religious policies during this period; and second, to contextualize their impact by examining the established religious practices within former villages and hamlets on a local level.